ICTV virus taxonomy profile: Potyviridae - Wylie, S.J.; Adams, M.; Chalam, C.; Kreuze, Jan F.; López Moya, J.J.; Ohshima, K.; Praveen, S.; Rabenstein, F.; Stenger, D.; Wang, A.; Zerbini, F.M. (Microbiology Society, 2017)
The Potyviridae is the largest family of RNA plant viruses, members of which have single-stranded, positive-sense RNA genomes and flexuous filamentous particles 680–900 nm long and 11–20 nm wide. There are eight genera, distinguished by the host range, genomic features and phylogeny of the member viruses. Genomes range from 8.2 to 11.3 kb, with an average size of 9.7 kb. Most genomes are monopartite but those of members of the genus Bymovirus are bipartite. Some members cause serious disease epidemics in cultivated plants.